Board Structure and Corporate’s Performance: Evidence from Private Education Companies - Mohd Razali, Mohd Waliuddin; Yau, Josephine Tan Hwang; Mohd Uzairi, Ahmad Hajazi; Janifer, Lunyai (Human Resource Management Academic Research Society, 2019)
This paper investigates the effect of board structure of Malaysian private educational companies towards their firm’s corporate performance. The average board size in this study is three and the percentage of women on board is about 40%. In addition, seventy six percent of the firm is having women as their director. By examining the relationship between board structure (board size and, woman on board) and the firm performance, our study shows that board size has a significant negative relationship with firm performance. However, women on board show significant positive effect on corporate performance. Our results imply that larger board will reduce firm performance, while women on board may create higher firm performance. These findings suggest that firm with large board size may encounter more agency issues in monitoring and controlling the members on board. On the other hand, firms with more women on board may have better corporate performance, as claimed by women are good in term of understand the market needs and bringing creativity and quality solution in decision making. More women in the board in some extent improve corporate performance in private education companies. The study could be extended with variables such as ownership, board meeting, director social network and other on corporate performance that could give significant interest of many stakeholders.